Management of mass casualty incidents: a systematic review and clinical practice guideline update - Höppchen, Arnold; Franke, Axel; Hertwig, Miriam; Gooßen, Käthe (European journal of trauma and emergency surgery, 2025)
Purpose Our aim was to generate evidence- and consensus-based recommendations for the management of mass casualty incidents (MCIs) based on current evidence. This guideline topic is part of the 2022 update of the German guideline on the treatment of patients with severe/multiple injuries. Methods MEDLINE and Embase were systematically searched to August 2021. Further literature reports were obtained from clinical experts. Randomised controlled trials, cross-sectional studies, prospective cohort studies, and comparative registry studies were included if they compared triage algorithms, interventions for MCI training, logistics or transport, decontamination, diagnosis or therapy during MCIs in the prehospital and hospital settings. We considered patient-relevant clinical outcomes such as mortality, diagnostic outcomes including sensitivity and specificity, rates of undertriage and overtriage as well as resource use. Risk of bias was assessed using NICE 2012 checklists. The evidence was synthesised narratively, and expert consensus was used to develop recommendations and determine their strength. Population, intervention, comparison, and outcome (PICO) questions from clinical questions were developed by clinical experts and guideline methodologists. Results We screened 321 records in the original guideline version and 4225 during this update. Twenty-five studies were included, all of them from the updated search from 2009 to 2021. Twenty-five new studies were identified. Interventions covered were triage training (n = 7 studies), prehospital triage (n = 6), secondary triage (n = 2), transport/logistics (n = 3), decontamination (n = 5), and therapy (n = 2) during MCIs. Three new recommendations were developed. All achieved strong consensus. Conclusion Due to unsatisfactory evidence, recommendations could only be made on training for improving triage quality and regular exercises for testing a hospital’s emergency response plan. No triage algorithm can be scientifically proven to be superior in all aspects. The key recommendation is the following: To improve triage quality, exercises or (virtual) training should be conducted in-house using verified triage systems and algorithms.
Online veröffentlicht: 10. Januar 2025
Gesehen am 07.07.2025